The Role of Students in Educational Activities for Mini Agrotourism Visitors at the Department of Food Security and Agriculture of Surabaya - Fitriana, Nisa Hafi Idhoh; Syukrillah, Dhealzy Rheynanda; Ramadhani, Firmansyah; Komariyah, Nur (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Edutourism is a program where participants travel to a place or area in a group to engage in a learning experience that is directly related to the destination. This educational tourism activity is carried out at the Mini Agrotourism, owned by the Surabaya City Food Security and Agriculture Service (DKPP), on Jl. Pagesangan Timur. This activity aims to discover the role of mentoring in improving visitors' understanding of the agricultural sector. The educational visit process through Goldenmelon includes creating an account, filling in data, selecting a destination, and uploading an application letter online until it gets approval from the officer. After that, the visit is carried out with the assistance of an officer, followed by reporting activities and periodic evaluations to improve services. The DKPP Surabaya Mini Agrotourism is an educational tourism destination that offers interactive activities such as plant introductions, cultivation practices, and interactions with livestock for all ages. We carry out activities in a structured manner and conclude with a satisfaction survey to evaluate our services. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 4: Quality EducationSDG 13: Climate Action